On the phylogeny and higher classification of the Oligochaeta - Jamieson, Barrie G. M. (Cladistics, 1988)
The 50 oligochaete taxa representing all families of “opisthoporous” oligochaetes (Aliuroididae, earthworms and aquatic “megadriles”) together with two representatives of the Haplotaxidae and three examples of “microdiles” were subjected to cladistic analysis using the PAUP program. Sixty-eight characters used in the analyses were derived from a comprehensive range of somatic and genital systems. The optimal result, in terms of maximal number of characters and taxa and of parsimony, produced two trees (consistency index 0.362) differing only in the placement of the monotypic clade for the family Lumbriculidae. From a line originating from the presumed octogonadial ancestor, the following branches were derived, in sequence from the basal to most derived (new taxa asterisked): subclass Randiellata* (order Randiellida*, Randiellidae); subclass Tubificata* (order Tubificida, Tubincidae, Naididae computed and others not computed); subclass Lumbriculata* (order Lumbriculida, Lumbriculidae); superorder Haplotaxidea* (order Haplotaxida, Haplotaxidae); order Moniligastrida (Moniligastridae); suborder Alluroidina (Alluroididae and Syngenodrilidae); cohort Aquamegadrili* (with, in succession, superfamily Sparganophiloidea, Sparganophilidae; Biwadriloidea, Biwadrilidae, and Almoidea—Lutodrilidae and Almidae, including Criodrilus); superfamily Eudriloidea*, superfamily Lumbricoidea and, as the adelphotaxon [brother taxon] of the latter, the superfamily Megascolecoidea. Intermediate nodes were given the following names, with the adelphotaxon through to the Megascolecoidea, M, in parentheses: subclass Diplotesticulata (Haplotaxidea—M); superorder Metagynopohora* [sic] (Moniligastrida—M); order Opisthopora (Alluroidina M); suborder Crassiclitellata* (Aquamegadrili — M); cohort Terrimegadrili* (Ocnerodriloidea M); unnamed (Eudriloidea M); unnamed (Lumbricoidea and Megascolecoidea). Recognition of the Randiellata, which alone were added intuitively and not computed, and the position of the Lumbriculata, are tentative. Location of the Lumbricoidea as the adelphotaxon of a restricted Megascoecloidea is heuristic, but the alternative depiction of lumbricoids in some analyses, as the adelphotaxon of an ocnerodrilid-eudrilid-megascolecoid clade (the conventional Megascolecoidea s. lat.), is not conclusively dismissed.
Annelida